IMPLEMENTATION OF RESTORATIVE JUSTICE BY JUDGES THROUGH THE IMMOSING OF CONDITIONAL CRIMINAL DECISIONS - Hibrawan, Aryatama (Universitas Sultan Ageng Tirtayasa, 2023)
The development of the criminal justice system has brought an approach that previously prioritized retaliation or was called retributive to recovery, which is better known as restorative justice. The retributive approach is considered to be no longer relevant as a solution to resolving criminal cases and is currently considered to cause other problems. In a restorative approach, criminal law aims to restore victims with equal responsibility by the perpetrator. In its development, a recovery-based approach began to be implemented by institutions that are members of the Criminal Justice System including judges through court decisions. A restorative approach through sentencing by a judge can be carried out by imposing a conditional criminal sentence. However, conditional criminal sentences are still very rarely applied, even though through this instrument judges can provide fair decisions that are needed by both victims and perpetrators.